PARTISIPASI LANSIA TERHADAP PELAYANAN KESEHATAN POSYANDU USILA ( Studi Deskriptif di Posyandu Usila Kecamatan Aek Ledong Kabupaten Asahan) - Agustina S.Sos (Departemen Sosiologi Universitas Sumatera Utara, 2012)
AGUSTINA Abstract : General development aims to transform people living better collar. One way of measuring the success of development by using measurements PQLI (Physiqal of Life Index). In the PQLI one indicator of success of development is the increasing life expectancy the number of people that from the increasing can be few number of elderly there. Increse of elderly if untreated the futured will bring problems of its own would development. This problem is related to social issues, health and productivited. To overcome these problems required the development program aimed at the elderly. One such program is the posyandu elderly health care. It these goals to improve the quality of life of older’s to remained productive in old age’s and also increase family’s awarned to care for the olderly. Respondents in this study are such many as 98 elderly respondent’s. The study also wanted to few how perceptions and participation in health care of elderly posyandu. The research was conducted in the Aek Ledong subdistrict, Asahan district. Research used in this research is by using quantitative research with descriptive approached. Data collection methods used are quesioner to deployment, documentation, and literature study. The data obtained and analyzed descriptively. Keywords : Posyandu, elderly, perception